Calculation model of mutual coupling between two ferrite-cored square coils in wireless power application for electric vehicles. (August 2020) - Zhang, Yameng; Zhang, Xi; Zhu, Chong; Cao, Dongpu
Abstract: Wireless power transfer (WPT) devices have been widely accepted by more and more industrial producers and consumers due to their safe, convenient, and high-efficient features. Square coils with ferrite cores are usually utilized as magnetic coupling devices by WPT systems for electric vehicles (EVs). However, the research on coupling coils often depends on three-dimensional finite element analysis (3-D FEA) tools such as ANSYS Maxwell or HFSS, which are troublesome and time-consuming. This paper explores a calculation model of mutual coupling between two square coils with ferrite cores based on magnetic mirror method. With this model, accurate results and fast operation speed can be obtained, and 3-D FEA tool is used to compare and verify the performance of this work.